Could Regional and Cantonal Banks Reduce Credit Risk through National Diversification? - Bertrand Rime (Swiss Journal of Economics and Statistics, 2007)
This paper evaluates the reduction of credit risk that can be achieved in Switzerland by a national diversification of bank lending. Using a credit risk model based on corporate default rates, I find that the risk of a nationally diversified loan portfolio is up to 20% smaller than the sum of the risks of regional portfolios. From a financial stability perspective, this substantial risk diversification potential should motivate particular scrutiny on the more than hundred Swiss banks staying on the regional business model.
Keywords: G21; G28; G31; 330; diversification; economic capital; consolidation